Multicultural and fun campus strategy - Rustamadji, Rustamadji; Triyoso, Anang; Maryanto, Eko Tavip (AMCA Journal of Education and Behavioral Change, 2023)
Globalization and increasing global uncertainty, cultural diversity has become one of the main factors affecting life. The difficulty of recruiting students due to the campus’ rigidity in adopting cultural diversity is a big loss. The steps for campus reform in adopting multi-culturalism need a strategy implemented by campus leaders to look forward. This paper aims to reveal the important factors that need to be implemented in the campus to get to the Multicultural Campus (CM). The method of writing this paper uses a qualitative approach which is supported by various conclusions from various multicultural research reports. In addition to the support of research reports, this paper is also a qualitative study of the implementation of CM that has been successfully carried out at the Muhammadiyah Education University of Sorong. The result is a CM creation strategy scheme by applying several important factors, namely vision, commitment, strategy and implementation. CM implementation includes Multicultural Campus Culture Creation, Multicultural Study and Development Center, CM Regulations, Multicultural Campus Facilities. In addition, there needs to be government support and multi-ethnic communities